IMPROVEMENT OF SOIL BEARING CAPACITY BASED ON MODERATE VOLUME USING RICE HUSK ASH - Tika Ermita Wulandari; Mitra Musika Lubis; Hermansyah (RADJA PUBLIKA, 2023)
Good soil is soil that has good stability and load-bearing capacity for any construction built on it. However, the existing soil conditions may not possess sufficient load-bearing capacity, necessitating a method to improve it. For instance, in North Sumatra, the soil is relatively soft and predominantly used for agriculture. Rice husk ash is a byproduct of rice farming and exhibits pozzolanic properties, making it a potential alternative for enhancing soil load-bearing capacity. Typically, soft soil is fine-grained, has high moisture content, high saturation, high porosity, high initial pore pressure, low shear strength, and significant potential for settlement under increasing effective stress. This research aims to improve soil load-bearing capacity by using rice husk ash with varying mixtures of 0%, 4%, 8%, 12%, 16%, and 20%. Soil samples were collected in the Lubuk Pakam area of North Sumatra. Testing included soil physical properties, such as soil index properties, and soil mechanics tests conducted in the soil mechanics laboratory at the University of Santo Thomas, Medan.Based on the tests, the soil was categorized as organic soil, highly cohesive, and had high plasticity. According to the USCS classification, it falls into the fine-grained or organic soil category with the symbol PT. The CBR values after 7 days of curing with various lime additions of 0%, 4%, 8%, 12%, 16%, and 20% were found to be 0.98, 1.18, 2.00, 4.80, 13.00, and 18.80, respectively. Therefore, it can be concluded that the higher the proportion of rice husk ash in the mixture, the higher the CBR value. This can potentially enhance farmers' income through rice husk sales.